Flaubert, les naturalistes rouennais et les théories biologiques de 1865 à 1880 - Bénédicte Percheron (Flaubert: Revue Critique et Génétique)
In 1865, while the spontaneous generation debate defended by Félix-Archimède Pouchet was about to end with Louis Pasteur’s victory, the one on the evolution of species began in Rouen. Among the first defenders of species variability, two of Gustave Flaubert’s friends figure prominently: Georges Pouchet and Georges Pennetier. These two personalities seemed to influence the writer directly, as scientific advisors, or indirectly, by their works and papers. Their correspondence can inform us on how the writer consulted Georges Pouchet for his work, but it tells us very little about between Gustave Flaubert and Georges Pennetier’s professional relationship. In this paper we will seek to elucidate the modalities of the scientific knowledge transfer between the naturalists and Gustave Flaubert.